Siyasah Al-Ighraq: A Case Study on Convection Market, Aur Kuning Bukittinggi - Rika Widianita; Andis Febrian; Syaiful Rahman (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
This research is motivated by the widespreed practice of siyasah al-ighraq (dumping) by traders in the Aur Kuning convection market in Bukittinggi in West Sumatera Provinve. Meanwile, siyasah al-ighraq(dumping) is haram in Islam. Therefore the author wants to examine how the siyasah al-ighraq (dumping) is carried out by traders in the Aur Kuning convection market in Bukittinggi, and how it impacts to market prices balance from an Islamic perspective. The method used in this study is descriptive qualitative with data collection techniques by conducting interviews with traders in the Aur Kuning convection market, Bukittinggi. The result showed that siyasah al-ighraq (dumping) practice by traders at the Aur Kuning convection market was only at certain times, such as during the month of ramadhan, after Eid al-fitr and the celebration of independence day. Siyasah al-ighraq are done just to use up old stocks that piled up. Then also dumping are carried out for new store promotion and as a marketing strategy. It dumping is called sporadic dumping, it is fine in Islam, because it doesn’t damage market price balance and doesn’t harm other traders. Dumping practice that haram in Islam are dumping that kill other people’s businesses and damage market price balance.